The Stability of Big-Five Personality Traits - Cobb-Clark, D; Schurer, S (My University, 2011)
We use a large, nationally-representative sample of working-age adults to demonstrate that personality (as measured by the Big Five) is stable over a four-year period. Average personality changes are small and do not vary substantially across age groups. Intra-individual personality change is generally unrelated to experiencing adverse life events and is unlikely to be economically meaningful. Like other non-cognitive traits, personality can be modeled as a stable input into many economic decisions.
Working Paper No. 21/11
IZA Discussion Papers
Keywords: Relationships -- Stability; Intergenerational Transfer -- Education; Beliefs and Values -- Personality; Identity; Intergenerational transfer; Learning, education and training; Beliefs and Values; Relationships; Intergenerational Transfer; Stability; Education; Personality; Learning, education and training; Intergenerational transfer; Identity